2006
DOI: 10.1152/japplphysiol.00143.2006
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the nucleus tractus solitarius and its influence on lung and airway reflexes

Abstract: The nucleus tractus solitarius (NTS) is the first central nervous system (CNS) site for synaptic contact of the primary afferent fibers from the lungs and airways. The signal processing at these synapses will determine the output of the sensory information from the lungs and airways to all downstream synapses in the reflex pathways. The second-order NTS neurons bring to bear their own intrinsic and synaptic properties to temporally and spatially integrate the sensory information with inputs from local networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 81 publications
1
42
1
2
Order By: Relevance
“…Previous studies have demonstrated that NTS neurons and their synapses can undergo homeostatic plasticity (reviewed by Bonham et al 2006). We therefore anticipated that vagotomy, by eliminating the propagation of action potentials from the visceral organs to monosynaptic NTS neurons, would cause a homeostatic, compensatory increase in synaptic efficacy at this first synapse.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that NTS neurons and their synapses can undergo homeostatic plasticity (reviewed by Bonham et al 2006). We therefore anticipated that vagotomy, by eliminating the propagation of action potentials from the visceral organs to monosynaptic NTS neurons, would cause a homeostatic, compensatory increase in synaptic efficacy at this first synapse.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed vagal NTS synapses and autonomic reflexes have been shown to undergo homeostatic plasticity in response to a number of different presynaptic insults (see review by Bonham et al 2006). In accordance with homeostatic compensation, we therefore expected an electrical stimulus to the ST to elicit an increase in the synaptic efficacy of monosynaptic NTS neurons following vagotomy.…”
Section: Vagotomy Causes a Decrease In Synaptic Efficacy At Monosynapmentioning
confidence: 94%
See 3 more Smart Citations